EFEK DIET ATEROGENIK TERHADAP GAMBARAN HISTOPATOLOGIS HATI MENCIT (Mus musculus) The Effect of Aterogenic Diet on Histopatology mice (Mus musculus) Hepar - Ervina Dewi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2019)
This research aimed to know the effct of aterogenic diet on histopatology mice hepar. The research was conducted from March to August 2017 at MIPA laboratory Jabal Ghafur University and Patology Laboratory FKH Syiah Kuala University. A experimental laboratory design was used with 2 treatments and 4 repetitions of each treatment. The treatments were standar weft (P0) and aterogenic diet weft (P1). Paraffin method was apllied of microscopic structure observation. The parameters observed were lipid infiltration, lipid degeneration and necrosis of mice hepatocyte. A T test was tested to the data alteration of histopatology of mice hepatocyte. The result showed that diet aterogenic could significant to increase lipid infiltration, lipid degeneration and necrosis of mice hepatocyte. In conlusion, the diet aterogenic has ability to increase lipid infiltration, lipid degeneration and necrosis of mice hepatocyte. Key word : diet aterogenic, lipid infiltration, lipid degeneration and necrosis, hepatocyte.